Acne Vulgaris and the Epidermal Barrier: Is Acne Vulgaris Associated with Inherent Epidermal Abnormalities that Cause Impairment of Barrier Functions? Do Any Topical Acne Therapies Alter the Structural and/or Functional Integrity of the Epidermal Barrier? - Thiboutot, Diane (Matrix Medical Communications, 2013)
Acne vulgaris is a common dermatological disorder that predominantly affects teenagers, but can also affect preadolescents and post-teen individuals. Despite the fact that acne vulgaris is the most common skin disorder encountered in ambulatory dermatology practice in the United States, there has been limited research on the epidermal permeability barrier in untreated skin of people with acne vulgaris and also after use of acne therapies. This article reviews the research results and discusses the available literature on this subject area. The importance of proper skin care as a component of the management of acne vulgaris is supported by the information that is currently available.